THE PRACTICE AND CHALLENGES OF IMPLEMENTING CRITICAL THINKING SKILLS IN EFL TEACHERS QUESTIONING BEHAVIOR - Ahmad Zainudin; Machdalena Vianty; Rita Inderawati (University of Kuningan, 2019)
The development of critical thinking is closely related to the questions asked by teachers as the teachers higher-order questions are cognitively demanding to promote students critical thinking. The purposes of this study are to investigate how critical thinking was implemented in EFL teachers questions in the classroom and the challenges faced by EFL teachers in integrating critical thinking questions. In addition, this study also investigated students reasons for non-response to particular questions asked by teachers. Applying mixed-method research design, the data were collected from classroom observation, interview, questionnaire and documentations. The research participants were two English teachers and 229 number of students of year 8. The results showed that the most dominant questions asked by the two English teachers were in Lower-order questions (78,8%), while the Higher-order questions were only (21,2%) questions. Second, the challenges faced by teachers were students intelligence has yet to reach the level of higher-order thinking, unconducive-classroom environment, teachers creativity itself, parental involvement and students lack of vocabulary. Third, dealing with the reason for students non-response in particular questions asked by teachers, there were some reasons, such as students are afraid of making mistakes, they could not put ideas into words, and lack of vocabularies. In conclusion, the teachers faced various challenges in implementing critical thinking questions in the classroom.